CAUSES AND PSYCHOSOCIAL CONSEQUENCES OF INTIMATE PARTNER VIOLENCE IN AMBO TOWN MARRIED WOMEN - FAYERA, MULISA; GETACHEW, ABERA (Innovare Journal of Social Sciences, 2021)
Intimate partner violence is a pattern of coercive tactics that can include physical, psychological, sexual, economic, and emotional abuses against intimate partners, with the goal of establishing and maintaining power and control. The aim of this study is to investigate intimate partner violence and associated factors in Ambo town. The participants of the study were household women between the age15 to 49. Data were collected by using both quantitative and qualitative methods. To collect the quantitative data, 389 household women of Ambo Town were randomly selected for closeended questionnaire. In qualitative method , 12 participants (six women were victims of IPV and six other married women) were purposely selected for semi structured and 10 key informants were also purposely selected for Focus group discussion. The data collected from the questionnaires were analyzed using descriptive and inferential statistical tools through SPSS.20 and the qualitative data was analyzed narratively. The results of the study demonstrated that from the total 389 sample, 343 women did not agree with their husband and only 46 women reported that they agree with their husband. This shows that there was a problem of disagreement between wives and their husbands. Besides, causes and psychosocial consequences of IPV were directly related with intimate partner violence.